Strategic Commodity Food Price Volatility in Central Java in 2020-2023 - Safitri, Mellyana (AIBPM Publisher, 2023)
This study aims to analyze the volatility of food prices, especially rice, in Central Java from 2020 to 2023. Food price volatility can have a negative impact on consumer welfare and costs. Indonesia, as a country that still imports basic food needs, is vulnerable to food price volatility. Spikes in food prices can cause inflation to rise and economic growth to decline, which impacts the condition of people's households, especially the poor. This research uses a quantitative method using ARCH GARCH timeseries data. The results of this study are expected to identify and analyze the volatility of rice food prices, predict rice food prices at the end of 2023, and determinex Bank Indonesia's policies related to rice food price volatility. This research is based on the concepts of volatility, food prices, and inflation. Quantitative methods such as ARCH and GARCH models are used to analyze the volatility of rice food prices. Secondary data is used in this study, and the research steps include data collection, data analysis and interpretation, and presentation of results to provide recommendations.